Interatrial Wall Abnormality is Associated with Adverse Same-Admission Outcomes Following Total Knee Arthroplasty - Zhang, Bruce B.; Uddin, Abdullah A.; Mai, David H.; Tozzi, Declan; Wolfert, Adam J.; Naziri, Qais (The Journal of Knee Surgery, 2024)
Total knee arthroplasty (TKA) is the most common joint arthroplasty procedure and is shown to be a reliable and efficacious way to improve quality of life. Individuals with interatrial wall abnormalities (IAWAs), such as atrial septal defect or patent foramen ovale (PFO), are at increased baseline risk for stroke and overall lifetime morbidity. The purpose of our study was to elucidate the association between IAWAs and perioperative TKA outcomes.We performed a retrospective cohort study utilizing the Healthcare Cost and Utilization Project National Inpatient Sample database. Admissions for TKA between 2010 and 2019 were identified using the international classification of disease (ICD)-9 and ICD-10 procedure codes. Patients with ICD-9-clinical modification (CM) diagnosis code 7455 or ICD-10-CM diagnosis code Q211 were assigned to the IAWA cohort, the primary exposure. Confounding variables included basic demographics, baseline health status, and surgical facility characteristics. The primary outcomes studied were medical complications, implant-related complications, and admission mortality. Univariate and adjusted multivariable regression analyses were used to identify associations.Compared to patients in the non-IAWA cohort, those in the IAWA cohort had significant risks for same-admission medical complications (odds ratio [OR] 5.77, 95% confidence interval [CI] 4.59–7.15; p < 0.001), implant-related complications (OR 1.55, 95% CI 1.09–2.12; p = 0.009), stroke (OR 77.46, 95% CI 58.4–101.2; p < 0.001), venous thromboembolism (VTE; OR 3.78 95% CI 2.47–5.51; p < 0.001), and mortality (OR 8.36, 95% CI 3.54–16.52; p < 0.001) following TKA.Compared to patients without IAWAs, those with IAWAs who undergo TKA have higher risks for same-admission medical and implant-related complications as well as same-admission mortality. Similarly, these patients have higher risks for same-admission stroke and VTE. Further research on perioperative TKA management in patients with IAWAs is needed.Level of Evidence is III: retrospective cohort study.
Keywords: atrial septal defect; patent foramen ovale; total knee arthroplasty; complications; outcomes; stroke; thromboembolism; mortality